Erosivity of rainfall and erosion losses under different management systems and crops covering in a reddish brown distrophic lateritic soil I. Second year results - Saraiva, Odilon E.; Cogo, Neroli P.; Mielniczuk, João (Pesquisa Agropecuaria Brasileira, 2014)
The effects of eight soil management systems on soil and water losses under natural rainfall conditions were evaluated at the Agronomic Experimental Station of the Rio Grande do Sul Federal Universtiy, in Guaíba, RS. A reddish brown distrophic lateritic sandy loam soil was utilized with 12% inclination. The observations were made from July 1976 to June 1977 on the following experimental plots: native grassland; cultivated pasture; two types of wheat-soybean double cropping in reduced tillage; bare soil in conventional tillage; double cropping wheat-soybean and wheat-corn in conventional tillage; and wheat-corn double cropping in reduced tillage. The rainfall erosivity index (El value) in the experimental period (July 1976 to June 1977) was 1,126.1. About 60% of this value occurred from January to March, 1977. The soil losses under pastures were very low. The bare soil showed the major loss of soil. Regarding soil protection against erosion, soybean was more efficient than corn, and corn was more efficient than wheat. The reduction of the soil tillage under soybean and corn was more efficient in controlling the erosion.
Keywords: erosivity index; soil erosion; soil and water losses; soil management; vegetal cover; natural pasture; glycine max; zea mays; triticum aestivum; trifolium vesiculosum